Tennis stroke precision and impact mechanics - Casolo, F.; Lorenzi, V. (2000)
Tennis racket precision is a controversial issue. It is evaluated only by experienced tennis players who express their perceptions during the stroke. Many parameters, such as frame stiffness, weight, mass distribution, string tension and ball properties certainly contribute to these perceptions. However, in order to determine their specific effects, racket precision needs be defined in objective mathematical terms. The precision of a flat stroke with a pre-impact trajectory normal to the string plane can be related to the post-impact ball trajectory angle. While this cannot claim to be the definition of racket precision, it may be one of its components. To analyze the influence of each mechanical parameter on this angle, an F.E. model of the system has been developed. This enables simulation of the rebound, including the impact phase, taking account of the ball, string tension, frame deformation and the player him or herself. The model can predict the ball trajectory and velocity after impact for several kinds of stroke, and also the equipment stress and strain. The computer simulation shows how the deflection of the stroke with respect to the pre-impact trajectory is related to the impact position, the mass distribution of the racket and the duration of the contact phase of the ball and racket during impact. It also indicates that the contact time is related primarily to the rigidity and internal pressure of the ball, and to the string tension. Preliminary tests show that, especially for off-center impacts, string tension plays opposing roles for stroke precision and power: with increasing tension the precision increases, but the rebound velocity decreases. The researchers conclude that the model is adequate for analysis of the impact phase and can be used to optimize the mechanical parameters of the racket for a specific player. It can also provide useful information on how ball characteristics may affect play.